Volume Kubus dan Balok Melibatkan Kemampuan Visualisasi Spasial di Kelas VIII - Reny Wahyuni; Ratu Ilma Indra Putri; Yusuf Hartono (Universitas Hamzanwadi, 2015)
This study was conducted to produce the learning trajectories in volume of cubes and cuboids involving spatial visualization ability eight grade . In this study involving eighth grade students of SMP YPI Tunas Bangsa Palembang academic year 2014 - 2015. The method used in this study is the type of research design validation studies that consists of three stages: preliminary, design experiments, and retrospective analysis. A series of learning instruments designed and developed based on allegations of learning and using PMRI approach. In this paper will discuss the pilot experiment phase. Activities carried out starting from the activities see the packaging to improve spatial visualization ability of students, conduct experiments to enter rubik and resolve problems related to daily life - today. The results showed that the activities of the learning process through a series of activities based on the experience has helped improve students' understanding of the concept the volume of cubes and cuboids.